Pemberdayaan Ibu-Ibu PKK RT 09/016 Kelurahan Mekarjaya Depok Melalui Pelatihan Hidroponik - Nurmala Dewi Qadarsih; Finata Rastic Andrari; Maimunah Maimunah (Community : Jurnal Pengabdian Pada Masyarakat, 2021)
Food is basic needs of human being. Everyone has a right to fulfil their food needs. In order to human food needs can be reach, it’s needs to do some effort. One of way is to create community food security. Depok is one of buffer zones for the Indonesia capital, which is very densely populated. With dense population, the availability of land is also very limited. For this reason, it is necessary to make a breakthought in the context of community empowerment through mothers by empowering limited land so that it can support family food security. One of the way is by socializing the hydroponic method to PKK mothers of RT 09/016 Kelurahan Mekarjaya Depok. Because with this hydroponic method, vegetables can be produced in limited land. From this socialization, it is hoped that mothers can apply it at home so that at least the family’s vegetable needs can be met from each family.